Fostering Tolerance Through Inclusive Islamic Education: The Role of Pesantren in Navigating Global Challenges - Mala, Asnal; Zulkarnain, Zulkarnain; Bakar, M. Yunus Abu; Marpuah, Siti (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
The study of fostering tolerance through inclusive education, particularly in Islamic boarding schools (pesantren), remains underexplored. This is partly due to the perception that Islamic education in Indonesia is still traditionalist, making it less appealing for in-depth research. The current dynamics and advancements of pesantren signify the growth of Islamic education in Indonesia, yet its role in addressing globalization is rarely discussed, especially concerning its capacity to navigate the global era. This research aims to explore how pesantren can adopt inclusive education principles to instill tolerance within Islamic education. It highlights the approaches pesantren employ to transmit tolerant Islamic knowledge while remaining sensitive to globalization and cultural shifts in the Islamic world. This study employs a qualitative approach using library research methods, drawing on primary and secondary data relevant to the themes of inclusivity, Islamic pedagogy, and pesantren education. A critical analysis technique is applied to examine themes of inclusivity and the challenges of globalization faced by pesantren. The findings reveal that pesantren have significant potential to promote inclusivity in addressing global challenges. The values fostered include at-ta’aruf (mutual understanding), at-tasammuh (tolerance), at-tawassuth (moderation), and ta’awun (mutual assistance), which help cultivate ukhuwah Islamiyah (Islamic brotherhood) and al-‘adl (justice), creating a harmonious learning environment. However, obstacles such as resistance to curriculum reform and strong traditionalist views within the pesantren community were also identified.